2017
DOI: 10.3389/fimmu.2017.01173
|View full text |Cite
|
Sign up to set email alerts
|

Lower Expression of MicroRNA-155 Contributes to Dysfunction of Natural Killer Cells in Patients with Chronic Hepatitis B

Abstract: MicroRNAs have been reported to be regulated in different ways in a variety of liver diseases. As a key modulator of cellular function in both innate and adaptive immunity, the role of miR-155 in chronic hepatitis B virus infection remains largely unknown. Here, we investigated the expression and function of miR-155 in chronic hepatitis B (CHB) patients. It was found that miR-155 expression in peripheral blood mononuclear cells (PBMCs) was lower in CHB patients than healthy controls (HC). Among CHB infection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In addition, researchers have found that miR-155-5p mediates T lymphocyte differentiation [26] and inhibits cell apoptosis [27]. In pathogenesis, miR-155-5p is associated with many diseases, such as cancer [28,29], cardiovascular disease [30], autoimmune disease [31], metabolic disease [32], and neurological disorders [33]. During HSV-1 infection, several studies have shown that the expression level of miR-155-5p is markedly increased by the viral infection [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers have found that miR-155-5p mediates T lymphocyte differentiation [26] and inhibits cell apoptosis [27]. In pathogenesis, miR-155-5p is associated with many diseases, such as cancer [28,29], cardiovascular disease [30], autoimmune disease [31], metabolic disease [32], and neurological disorders [33]. During HSV-1 infection, several studies have shown that the expression level of miR-155-5p is markedly increased by the viral infection [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that NK cell surface receptors, killing effector molecules, and proliferation are regulated at multiple levels, such as miRNA, lncRNA, or Jak-Stat signaling pathway. We hypothesize that propofol may be involved in the regulation of NK cells at these levels, but the specific mechanisms remain to be further studied [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of immune‐active patients among those with hepatitis B virus (HBV) infection found the miR‐155, a positive regulator of IFN‐γ in NK cells, was expressed much lower in patients than in healthy controls. In response to HBV infection in patients, down‐regulation of miR‐155 impaired IFN‐γ secretion through targeting suppressor of cytokine signaling 1 (SOCS1) in the JAK/STAT signaling pathway . Positive regulators of IFN‐γ, such as miR‐181[54] and miR‐155, together with the negative regulator miR‐146, balance the expression of IFN‐γ in NK cells during the immune response.…”
Section: Gene Regulation By Microrna In Nk Cellsmentioning
confidence: 99%